Effects of diabetes nutrition education on glycemic control and diabetes-related outcomes among individuals with Type 2 Diabetes Mellitus at selected health clinics in Padang, Indonesia - Puri, Ice Yolanda (2022)
While structured nutrition education is vital for patients with Type 2 Diabetes (T2DM), comprehensive studies that look into the patient and the nutritionist's needs in developing and evaluating the appropriate nutrition education tools in Indonesia are scarce. Thus, this study was conducted to determine the effects of diabetes nutrition education (DNE) on glycemic control and other-related outcomes among patients with T2DM at selected health clinics in Padang, Indonesia. The study consisted of three phases based on Generalized Model for Program Planning and during the COVID-19. Phase I involved a cross-sectional need assessment survey with nutritionists (n=48) and patients (n=179) in Padang City. Phase II focused on developing and assessing DNE modules and materials based on the Health Belief Model (HBM). Phase III was a cluster randomized controlled study involving eight Public Health Centers (PHC), with 150 participants in the Intervention Group (IG; N=75) and Control Group (CG; N=75). The IG received a structured 7 sessions of DNE delivered by nutritionists at an individual level for every month within the first 3 months and came for follow-up at 6 months. Participants in the CG continued attending the regular sessions delivered by the nutritionists for the same study period. Primary outcomes measure included glycemic control (HbA1c and fasting blood glucose (FBG)), and secondary outcomes were diabetes-related, which included the nutritional status (anthropometry, blood pressure, dietary intake), knowledgeattitude practice (KAP) regarding diabetes management, and quality of life (QoL). The Phase I study identified leaflets (93.8%) as the primary material for nutrition education. The nutritionists (52.1%) were also concerned that their patients were reluctant to attend the education sessions and about 20.8% of them reported that the current materials were insufficient to attract interest, which highlighted the need to develop the DNE. In fact, nearly half of patients with T2DM (42.3%) did not attend the nutrition education session since their doctor did not refer them to the nutritionists. In Phase III, Baseline characteristics between the groups were comparable except for fiber intake and knowledge component in KAP, which was better in IG. At the end of 6 months, like CG, participants in IG did not improve their HbA1c, FBG, anthropometric data, and QoL, which were no different from CG. Nonetheless, a more significant improvement was observed in IG than CG for diastolic blood pressure (BP), level of KAP regarding Diabetes Management, and the component of dietary intake (energy and dietary carbohydrate, fat, and fiber). Concurrently, participants in CG achieved a substantial systolic BP improvement compared to IG participant. In conclusion, the study highlighted the need to have structured diabetes nutrition education for T2DM patients from patients themselves and nutritionists, which led to the DNE development. The delivery of DNE had shown improvement in diastolic BP and KAP regarding Diabetes Management and dietary intake. The patients and the nutritionists well accepted the DNE.